Young American Muslims Dynamics of Identity - Kabir, Nahid Afrose (Edinburgh University Press, 2012)
What is it like to be a young Muslim in America? Many young Americans cherish an American dream, 'that all men are created equal. And the election of America's first black President in 2008 has shown that America has moved forward. Yet since 9/11 Muslim Americans have faced renewed challenges, with their loyalty and sense of belonging being questioned. Nahid Kabir takes you on a journey into the ideas, outlooks and identity of young Muslims in Florida, Maryland, Massachusetts, Michigan, New York and Virginia. Based on around 400 in-depth interviews with young Muslims, discover the similarities and differences between ethnic and racial groups such as Iranians, Arab Americans and African Americans. Find out how they rate President Obama as a national and world leader, where they stand on the Israeli-Palestine issue and how the media impacts on them.
Description based on print version record.
KU Select 2018: HSS Backlist Books
Keywords: Religion / Islam; Social Science / Ethnic Studies; Social Science / Minority Studies; Social sciences; Electronic books